Anti‐inflammatory activity of green versus black tea aqueous extract in a rat model of human rheumatoid arthritis. (12th May 2015) - Ramadan, Gamal; El‐Beih, Nadia M.; Talaat, Roba M.; Abd El‐Ghffar, Eman A.
Abstract: Aim: Recently, there has been an increasing interest in tea ( Camellia sinensis ) as a protective agent against inflammatory diseases. Here, we evaluated/compared the anti‐inflammatory activity of two different doses (0.5 and 1.0 g/kg body weight) of green tea aqueous extract (GTE, rich in catechins) and black tea aqueous extract (BTE, rich in theaflavins and thearubigins) in rat adjuvant‐induced arthritis (AIA). Methods: Adjuvant‐induced arthritis rat model received orally/daily distilled water as vehicle, indomethacin (1.0 mg/kg body weight; a non‐steroidal/anti‐inflammatory drug), or tea aqueous extracts (for 28 or 14 consecutive days starting from day 0 or 14 of arthritis induction, respectively). Results: The present study showed that only the high dose of GTE (from day 0) significantly alleviated ( P < 0.05–0.001) all complications shown in arthritic rats, including synovial joint inflammation, elevation in erythrocyte sedimentation rate, blood leukocytosis (due to lymphocytosis and neutrocytosis), and changes in weight/cellularity of lymphoid organs. The anti‐arthritic activity of the high dose of GTE (from day 0) was comparable ( P > 0.05) with that of indomethacin (12.9–53.8 vs . 9.5–48.4%, respectively) and mediated by significantly decreasing and down‐regulating ( P < 0.001) the systemic production of pro‐inflammatory cytokines and the expression of chemokine receptor‐5 in synovial tissues, respectively. Moreover, the anti‐arthritic activity of tea aqueous extracts was in the following order: high dose of GTE > low dose of GTE ≥ high dose of BTE > low dose of BTE. Conclusion: The present study proved the anti‐inflammatory activity of GTE over BTE and equal to that of indomethacin in AIA rat model.